2018
DOI: 10.15611/aoe.2018.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Room rate parity vs. Rate fences in the context of price discrimination theory: the case of the Polish hospitality market

Abstract: Rate parity is still a very controversial issue, thus many researchers and industry professionals study it with respect to several aspects: whether it is beneficial for the hotel and/or for the customers. However, despite the necessity to respect rate parity, many hotels do not apply this requirement. Therefore, the authors have attempted to assess this phenomenon in the Polish hospitality market. The aim of the study was to determine the scope of applying rate parity by Polish hotels and using the price discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Differential pricing is the strategy of charging different prices for the same category of rooms to different guests depending on the booking channel, booking volume and booking timing (Biełuszko & Marciszewska, 2018;Lii & Sy, 2009;Suklabaidya & Singh, 2017). Furthermore, hotel rooms are considered 'perishable goods' therefore hoteliers use a variety of room pricing techniques such as high-demand and low-demand tactics to try to optimize revenue for the hotel (Napierała & Leśniewska-Napierała, 2022).…”
Section: Differential Pricing In the Hotel Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…Differential pricing is the strategy of charging different prices for the same category of rooms to different guests depending on the booking channel, booking volume and booking timing (Biełuszko & Marciszewska, 2018;Lii & Sy, 2009;Suklabaidya & Singh, 2017). Furthermore, hotel rooms are considered 'perishable goods' therefore hoteliers use a variety of room pricing techniques such as high-demand and low-demand tactics to try to optimize revenue for the hotel (Napierała & Leśniewska-Napierała, 2022).…”
Section: Differential Pricing In the Hotel Industrymentioning
confidence: 99%
“…The survey was conducted based on 367 responses Booking timing (BT) Tomalieh ( 2014), Lii and Sy (2009) The study demonstrated how booking volume and combination price discrimination impacted the marketing performance of hotels Booking volume (BV) Biełuszko and Marciszewska (2018), Abdel-aleem (2017), Choi and Mattila (2009) The study ascertained how far hotels may use rate parity and price discrimination across a range of direct and indirect electronic distribution channels Booking channel (BC) Ali et al (2021), Sujay and Afza (2019), Sadeghi et al (2017), Kondasani and Panda (2015) The authors revealed that customer satisfaction and behavioural intentions such as recommendations, loyalty and willingness to pay can be impacted by PSQ. The survey was conducted in three-, four-and five-star hotels Perceived service quality (PSQ) Sujay and Afza (2019), El-Adly (2019), Ali et al (2017) The authors highlighted how the dimension of service quality significantly influences the prediction of customer satisfaction.…”
Section: Authors and Dates Brief Overview Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, guests pay lower prices, reduced by online mediation commission fees and, in return, hotels offer a variety of facilities to their regular guests, thus benefiting all stakeholders. Biełuszko and Marciszewska (2018) explored the topic area of prices, tackling the issues of rate parity, price management and differentiation, as well as rate fences which hotels use in order to improve the competitiveness of their price in relation to other commissionable distribution channels.…”
Section: Contemporary Trends In the Hotel Distribution In Europe Theoretical Backgroundmentioning
confidence: 99%
“…An objective fact closely related to the development of China's tourism industry is that China's Internet and its applications have made remarkable achievements in the world and become a "booster" to improve the quality of China's economic development and promote supply side reform. Because of artificial intelligence technology, the traditional mathematical-statistical model has strict requirements on assumptions and sample data categories when the model is applied to practice, and only using mathematical formulas and theories to describe enterprise business performance can not comprehensively and effectively explain the complex and changeable situation faced by enterprises in the real society, resulting in the reduction of the accuracy and reliability of model classification and evaluation [11,12].…”
Section: Introductionmentioning
confidence: 99%